(untitled) (Per Musi, 2014)
The repercussion among authors and readers of the previous issues 22 and 23 of Per Musi (classified with QUALIS A1 by CAPES and indexed in SciELO), dedicated to studies in popular music, motivated another call on this theme, which seems to be the one that has most attracted the attention of researchers in the recent history of research in music in Brazil. Due to the large number of submissions, the approved articles were divided into three volumes - 28, 29 and 30 - which bring a total of 46 articles, 11 scores and 6 reviews. This volume 29 of Per Musi contains 19 articles, 2 scores and 1 review.